Culture for Creativity in Hospitality Industry in Nepal - Maharjan, Pushpa (PYC Nepal Journal of Management, 2016)
This paper examines the relationships between the culture and creativity in the business enterprises of sectors such as hotel, travel and trekking agencies. The survey was conducted in the month of November 2015 in Kathmandu valley. The data analysis was based on data collected from self-administered questionnaires. Of the 150 questionnaires distributed to the respondent-employees, 126 responses were usable making the response rate of 84 percent. The study concludes that collaboration is more important factor than trust and learning for creativity in Nepalese hotels, travel and trekking agencies.